Repercussions of Sustainable Agricultural Productivity, Foreign Direct Investment, Renewable Energy, and Environmental Decay: Recent Evidence from Latin America and the Caribbean - Naseem, Sobia; Hui, Wang; Sarfraz, Muddassar; Mohsin, Muhammad (Frontiers in Environmental Science, 2021)
This research aims to assess and implement the long and short-run relationship of agriculture and environmental sustainability with control variables. Purposely, this research consolidates theoretical and conceptual principles to create a systematic structure in agriculture for the development of both sectors, i.e., agriculture and the environment. On this ground statement, this research is motivated to contemplate the relationship between carbon dioxide emission, agriculture production, gross domestic product, renewable energy consumption, and foreign direct investment by using annual data series of the Latin American and Caribbean countries from 1971 to 2018. The ARDL is used as an econometric methodology to check the relationship among variables. Agriculture is the most vulnerable sector in the Latin American and Caribbean countries, and the economy is heavily dependent on it. The main results of this research indicated that agriculture and CO2 emission are positively related to each other for the long and short-run means that agricultural activities increase the CO2 emission level. At the same time, control variables show mixed association with environmental degradation as GDP is positively significant and renewable energy consumption is negatively significant. The Error Correction (ECt-1) term is negatively significant, confirming the long-run relationship and speed of adjustment from short to long-run equilibrium. Agriculture production and gross domestic product lead to increment in CO2 emission while renewable energy consumption is negatively contributed to toxic emissions. The speed of adjustment in the Latin American and Caribbean countries is nippy. It requires 2.933 periods to the transformation from short periodic phase to long-term. A comprehensive approach is the research debate rigorously and holistically based on divergent sectors of an economy and their relationship with environmental sustainability. The econometric method, symbolic system, and conceptual existence were designed originally.